1997
DOI: 10.1002/(sici)1097-4547(19970901)49:5<515::aid-jnr1>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

The nucleus accumbens and learning and memory

Abstract: Recent research on the nucleus accumbens (NA) indicates that this brain region is involved in learning and memory processes in a way that is separable from its other well-known roles in behavior, such as motivation, reward, and locomotor activity. These findings have suggested that 1) the NA may be involved in declarative, or hippocampal formation-dependent learning and memory, and not in several other non-declarative forms of learning and memory, and 2) the NA may be selectively involved in certain stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…Much previous evidence has implicated the NAc in appetitive Pavlovian and instrumental learning (1,2,31) in ways that are readily distinguishable from its well known involvement in motivation, reinforcement, and motor activity (32). In particular, the NAc has been implicated in the acquisition and͞or consolidation of spatial information but not in its retrieval (1,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much previous evidence has implicated the NAc in appetitive Pavlovian and instrumental learning (1,2,31) in ways that are readily distinguishable from its well known involvement in motivation, reinforcement, and motor activity (32). In particular, the NAc has been implicated in the acquisition and͞or consolidation of spatial information but not in its retrieval (1,33).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the NAc has been implicated in the acquisition and͞or consolidation of spatial information but not in its retrieval (1,33). In intact rats, place learning in the aversively motivated Morris water maze is impaired by pretraining intra-NAc infusions of haloperidol (34) and by posttraining intra-NAc infusions of sulpiride (3) and AP-5 (7), but not by posttraining intra-NAc infusions of the AMPA receptor antagonist DNQX (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect, however, that it is relatively unlikely that intra-NAc infusions of LY379268 selectively interfered with memory retrieval. In a review of the literature on the role of the NAc in learning and memory, Setlow (1997) concluded that 'ythe NAc is involved in learning and/or consolidation, but not in retrieval, suggesting that the NAc is a permanent site of memory storage' (p 517). For example, Sutherland and Rodriguez (1989) found that prior to training, lesions of the NAc impaired learning in a spatial version of the Morris water-maze task; however, when lesions were performed post-training, they had no effect on task performance, see also Ploeger et al (1994), but see Seamans and Phillips (1994) for different results in a study using a radial arm-maze task.…”
Section: Psychological Mechanisms Underlying the Effect Of Ly379268 Nmentioning
confidence: 99%
“…The nucleus accumbens (NAc) and its associated circuitry have been linked to the acquisition of adaptive motor responses and the control of behaviors related to natural reinforcers (Setlow 1997;Parkinson et al 2000;Corbit et al 2001). Because of the rich glutamatergic and dopaminergic innervation of the NAc from regions associated with motivational, cognitive, and sensory processes, many studies have focused on the role of these neurotransmitter systems with respect to instrumental and incentive learning (Berridge and Robinson 1998;Cardinal et al 2002;Beninger and Gerdjikov 2004;Kelley 2004).…”
mentioning
confidence: 99%